TANGGUNG JAWAB PEMERINTAH DALAM MENJAMIN AKSES HUKUM YANG ADIL BAGI UMKM - Oktaviani, Putri; Ulhaq, Dzaki Dhiya; Manurung, Yerikho Alfredo; Daksa, K Prabu Bhara (Ensiklopedia Sosial Review, 2025)
Abstract: Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s national economy, contributing significantly to Gross Domestic Product (GDP) and employment absorption. However, in practice, MSMEs still face disparities in accessing the legal system and regulations that should protect and empower them. These disparities are evident in various aspects, including limited legal information, lack of legal representation, and unequal legal protection compared to large business actors, such as modern retail and multinational companies. This inequality ultimately hinders the healthy and sustainable growth of MSMEs. Therefore, the government holds a strategic role and constitutional responsibility to ensure fair and proportional legal access for all business actors, particularly MSMEs, which are structurally in a weaker position. This study aims to examine the government’s responsibility in ensuring legal justice for MSMEs in Indonesia and to analyze the normative and practical obstacles encountered in fulfilling that responsibility. A normative juridical approach is used in this research by reviewing relevant legislation, such as Law Number 20 of 2008 on MSMEs, Presidential Regulation Number 112 of 2007 on the Structuring and Development of Traditional Markets, Shopping Centers, and Modern Stores, and other implementing regulations. In addition, a limited empirical approach is employed through literature review and secondary data analysis on the implementation of government policies in supporting MSMEs. The findings indicate that the government has undertaken several affirmative measures to strengthen MSMEs' legal standing, such as simplifying licensing procedures, facilitating access to financing, and mandating business partnership quotas between MSMEs and modern retailers. However, these policies have not fully addressed the substantive legal access needs due to persistent disparities in implementation at the regional level. Key contributing factors include weak coordination between central and local governments, low legal literacy among MSME actors, and the lack of dedicated legal assistance institutions for MSMEs. Moreover, the imbalance of bargaining power between MSMEs and large business entities results in exploitative partnership agreements that MSMEs find difficult to contest without adequate legal support. The government’s responsibility to ensure fair legal access for MSMEs is a constitutional mandate inseparable from the goals of national development. Fair legal access not only entails formal equality before the law but also includes the actual ability of MSMEs to understand, utilize, and benefit from the legal system. The government must commit to strengthening its regulatory, facilitative, and protective roles in building a legal system that supports small enterprises while ensuring structural justice in every economic policy implemented.Keywords: legal access, MSMEs, legal disparity, government role, economic justice.